Do cognitive processes and motives for argumentative writing converge in writer profiles?. Issue 4 (6th October 2022) - De Smedt, Fien; Landrieu, Yana; De Wever, Bram; Van Keer, Hilde
Abstract: The aim of this study is twofold: (1) to distinguish writer profiles on the basis of students' cognitive processes and motives for argumentative writing and (2) to study differences in the distribution of students' background characteristics and in students' writing outcomes across writer profiles. Participants were students who are enrolled in the academic track of upper-secondary education (aged 16–18). The current study uses questionnaire data from two independent samples ( n sample 1 = 386 students; n sample 2 = 383 students) and writing test data from sample 1. A hierarchical and k -means cluster analysis was conducted on both samples revealing two clusters: (1) process-oriented writers with a high autonomous writing motivation and (2) writers who reported overall lower levels of cognitive writing processes and who simultaneously were less autonomously motivated to write. Furthermore, we found statistically significant differences between the writer profiles in terms of gender distribution and the results also showed that profile 1 students felt significantly more self-efficacious in argumentation and in regulating their writing behavior compared to students in profile 2. The present study contributes to the limited amount of person-centered profiling studies in writing research, especially since no studies to date have investigated writer profiles by combining cognitive and motivational cluster variables.